Návrh podpory řízení zakázky - Vavrouchová, Anna (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Tato diplomová práce se zabývá návrhem konfigurátoru solenoidových ventilů pro podporu řízení zakázky a procesu prodeje. Řešení je založeno na detailní analýze řízení zakázky ve vybrané strojírenské společnosti.

This thesis deals with the design of a solenoid valve configurator to support the order management and sales process. The solution is based on a detailed analysis of order management in a selected engineering company.
Design of Order Management Support
Keywords: řízení zakázky; procesní řízení; konfigurátor ventil; business process management; digitalizace; order management; process control; valve configurator; business process management; digitalization